Regioselectivity in the Ring Opening of Epoxides for the Synthesis of Aminocyclitols from D-(-)-Quinic Acid - Shu-Yu Yang; Tzenge-Lien Shih (Molecules, 2012)
Efficient syntheses of four aminocyclitols are reported. Each synthesis is accomplished in eight steps starting from D-(-)-quinic acid. The key step involves a highly regioselective ring opening of epoxides by sodium azide.